6-(v-3)=9(2v+3)

Simple and best practice solution for 6-(v-3)=9(2v+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(v-3)=9(2v+3) equation:


Simplifying
6 + -1(v + -3) = 9(2v + 3)

Reorder the terms:
6 + -1(-3 + v) = 9(2v + 3)
6 + (-3 * -1 + v * -1) = 9(2v + 3)
6 + (3 + -1v) = 9(2v + 3)

Combine like terms: 6 + 3 = 9
9 + -1v = 9(2v + 3)

Reorder the terms:
9 + -1v = 9(3 + 2v)
9 + -1v = (3 * 9 + 2v * 9)
9 + -1v = (27 + 18v)

Solving
9 + -1v = 27 + 18v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-18v' to each side of the equation.
9 + -1v + -18v = 27 + 18v + -18v

Combine like terms: -1v + -18v = -19v
9 + -19v = 27 + 18v + -18v

Combine like terms: 18v + -18v = 0
9 + -19v = 27 + 0
9 + -19v = 27

Add '-9' to each side of the equation.
9 + -9 + -19v = 27 + -9

Combine like terms: 9 + -9 = 0
0 + -19v = 27 + -9
-19v = 27 + -9

Combine like terms: 27 + -9 = 18
-19v = 18

Divide each side by '-19'.
v = -0.9473684211

Simplifying
v = -0.9473684211

See similar equations:

| 7(6x-7)+1=42x | | 10x^2-25x^3=0 | | 8+2n+1= | | x+15=420 | | x^2+14x-150=0 | | 7x=2y-7 | | 6+5(X-5)=2-8(X-5) | | 6+5(X-5)=2-2(X-5) | | -3=x^2+3x+5 | | 3x+7+5x-3=90 | | 64y^2-36=0 | | 3x+7+5x-3=180 | | 2x+14=4x-6 | | 0=60.5+13.3t-4.9t^2 | | x^2+10x+8y+41=0 | | 19x+6=32+4x | | 17=37+4 | | 10t^2=5 | | 5c+24=4 | | x+2x+17=80 | | (9x^2)-18x+9=47 | | 13+3p=9 | | x-2+x+x+3=34 | | (49x^2)+14x+1=9 | | h+h+14=306 | | t+2t=5+7 | | -16t^2+18=10 | | (16x^2)+2x-3=0 | | x-1+x+x+2=37 | | -2b+4=3b | | Qs=-20+3 | | (2x^2)+12x=0 |

Equations solver categories